SWOT-TOWS analysis of an electronic health referral system: basis for development strategy - Emmanuel Carlos Navarro; Cristina Enriquez Dumdumaya (International Journal of Advances in Applied Sciences, 2026)
Along with the implementing rules and regulations of Republic Act No. 11223 (Universal Health Care Act) and the national mandate for the digital transformation of basic services, the Philippine health sector faces the imperative to implement an interoperable electronic referral (eReferral) system. This study applies strengths, weaknesses, opportunities, threats (SWOT) and threats, opportunities, weaknesses, strengths (TOWS) to conduct a SWOT–TOWS strategic analysis of internal and external factors affecting the existing healthcare referral system and to generate evidence-based strategies for national eReferral system adoption. The analysis identifies strong policy support and institutional frameworks as key enablers, while fragmented information and communication technology (ICT) infrastructure, absence of Health Level Seven International (HL7)/Fast Healthcare Interoperability Resources (FHIR) interoperability standards, limited bandwidth in rural facilities, and insufficient technical personnel constitute primary barriers. Comparative benchmarking against the UK NHS eReferral service and US EHR-based referral systems highlights critical design gaps in the Philippine context. The proposed strategies, encompassing a centralized system architecture, ICT readiness investments, and compliance with ISO/IEC 27799 health informatics security standards, provide an actionable framework for policymakers, ICT planners, and healthcare administrators. This study contributes to health informatics literature by applying strategic analysis to health IT system design as a novel methodological intersection.